Diabetes-associated neutrophil NETosis: pathogenesis and interventional target of diabetic complications - Zhu, Yuyan; Xia, Xuan; He, Qian; Xiao, Qing-Ao; Wang, Decheng; Huang, Meirong; Zhang, Xiaolin (Frontiers in Endocrinology, 2023)
Neutrophil extracellular traps (NETs) are known as extracellular fibers networks consisting of antimicrobial proteins and decondensated chromatin DNA released by activated neutrophils. NETosis is a NETs-induced neutrophilic cell death which is unique from necrosis or apoptosis. Besides its neutralizing pathogen, NETosis plays a crucial role in diabetes and diabetes-related complications. In patients with diabetes, NETs-releasing products are significantly elevated in blood, and these findings confirm the association of NETosis and diabetic complications, including diabetic wound healing, diabetic retinopathy, and atherosclerosis. This article briefly summarizes the mechanisms of NETosis and discusses its contribution to the pathogenesis of diabetes-related complications and suggests new therapeutic targets by some small molecule compounds.